AFLI Indicators for Measuring Library Performance: An Analytical Developmental Study - Emad Abu Eid (Cybrarians Journal, 2018)
The objective of this study is to provide improvement opportunities for the Arab Federation of Libraries and Information (AFLI) indicators to measure library performance. The researcher used the analytical descriptive method, in which described and analyzed the performance indicators of the first edition of the AFLI Iindicatorsissued in 2013. National, regional and international standards have received considerable attention in various professional areas. They aimed to raise and standardizelibrary works. They are widespread and applied in various library fields. AFLI aims to achieve its goals on the ground to all types of libraries in the Arab world.Challenge that arisesis to what extent libraries can benefit from these standards, adopt them and ability of to apply them.Accordingly, the question appears about availability of mechanisms of implementation including awareness, training and capacity building for the development, improvement, upgrading and empowerment of libraries.